Implementasi Permen PAN-RB No. 28 Tahun 2019 Tentang Penyetaraan Jabatan Administrasi Ke Jabatan Fungsional Di Lingkungan BKKBN Provinsi Kalimantan Selatan - Marsella, Ariyati (Professional: Jurnal Komunikasi dan Administrasi Publik, 2025)
This study aims to understand the implementation of the Regulation of the Minister of State Apparatus Empowerment and Bureaucratic Reform Number 28 of 2019 related to the equalization of administrative positions to functional positions within the BKKBN Representative of South Kalimantan Province. With a qualitative approach and descriptive methods, this study relies on interviews, observations, and documentation as data collection techniques, while informants are the main source of information. The data is analyzed through the process of reduction, presentation, and conclusion drawn. The results of the analysis show that the implementation of this policy is still not optimal. Based on Edward III's policy implementation theory, it was found that the variables of communication, resources, disposition, and bureaucratic structure have not reached ideal conditions. This research also highlights the role of policy implementers and the impact of policies on relevant officials. As a recommendation, the Representative of the South Kalimantan Provincial BKKBN needs to improve the work system in functional positions to ensure that policies can run more effectively and in accordance with applicable regulations, so as to support bureaucratic efficiency.